PENGETAHUAN MASYARAKAT TENTANG PENCEGAHAN HIV AIDS DI DUSUN KEDUNGPOH LOR, NGLIPAR - Sofiana, Liena; Azhari, Muhammad Atqia; Sari, Dwi Putri S Retni; Stefani, Devi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
HIV/AIDS is a disease that continues to grow and become a global problem that is sweeping the world. At the end of 2016, it was estimated that 36.7 million people in the world were living with HIV, as many as 1.8 million people were newly infected with HIV. Yogyakarta ranks 14th in the number of HIV/AIDS from 34 provinces in Indonesia in 2015, with 531 HIV cases and 91 AIDS cases. The high cases in some areas can be caused by low knowledge. Based on data analysis activities carried out in the Dusun Kedungpoh Lor, it was found that the people in the Dukuh Kedungpoh Lor had low knowledge of the problem of HIV/AIDS, as many as 72.83% of the people who had low knowledge of HIV/AIDS. Intervention activities carried out using extension methods with the aim of increasing public knowledge about HIV/AIDS prevention and control. This counseling was carried out on February 24, 2019 at the hall in Dusun Kedungpoh Lor with 31 participants. This counseling went smoothly seen in the enthusiasm of residents when attending discussions and questions and answers. The results that there was an increase in knowledge about HIV prevention and control after counseling.